Automatic temperature control system for aquaponic green house - Amin Khairi, Rosli (2013)
The objective of this thesis is to design an automatic temperature control system in the aquaponic house. This project focuses on the design of control systems using the concepts of temperature control using PIC and low cost. The purpose of this project is to overcome the problems occurred in the heat of the house aquaponic to control the flow of ventilation as a cooling agent. In this project, PIC16F876A is used as the brain for the prototype. PIC controls were selected as a control because it has a faster response when compared with conventional control on-off. The components required in this project can be divided into two groups, electric components and mechanical components. Some electrical components used are actuator, switches, relays and PIC controller. Mechanical components used were as bolts and nuts as well as the mechanical structure. The system completed and tested to control the temperature constant 30°C.